THE ROLE OF LOCAL WISDOM AS PART OF CORRUPTION ERADICATION STRATEGY - LIM KURNIAWAN SETIADARMA (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACT Corruption has been a pervasive problem plaguing our country for a long time. On the other hand, raising community awareness and enhancing public participation have been acknowledged as part of the corruption prevention and eradication strategy in Indonesia for many years, especially since the enactment of 1999 Corruption Law. Nonetheless, public participation in the country seems to keep decreasing throughout the years, leaving corruption alone eroding every sector of society. For this reason, it is important to realize that the success level of public participation is highly related to the existing beliefs and values of people that are expected to be participating – the local wisdom. The purpose of this paper is to evaluate the effectiveness of public participation in eradication of corruption, assess whether the local wisdom has been supporting the corruption eradication/prevention strategy, and finally conclude with a proposition to maximize the role of local wisdom in combatting corruption in Indonesia. To achieve that goal, delving into applicable laws, general principles of law, journals and books, cases and reports, as well as various surveys becomes very important to increase the knowledge and objectivity in thinking and analyzing. Two surveys were also conducted to Indonesian citizens with 328 respondents and 495 respondents, in order to see the real cultures and beliefs that are currently developing in Indonesian society. This research paper will reveal the current Indonesian local wisdom on the ground and its connection to the large strategy of corruption eradication at national level.